ChemInform Abstract: Ti‐Mediated Intramolecular Cyclopropanation of N‐Alkenyl Thioamides: Scope and Mechanistic Study. Issue 42 (14th October 2014) - Hermant, Fabien; Nicolas, Emmanuel; Six, Yvan
Abstract Treatment of thioamide substrates with a Grignard reagent and Ti(OiPr)4 results in the formation of bicyclic aminocyclopropanes.